2009
DOI: 10.1080/00288330909510015
|View full text |Cite
|
Sign up to set email alerts
|

A vessel‐deployed passive postlarval collector to assess settlement of the American lobsterHomarus americanus

Abstract: Passive collectors are used widely in postlarval settlement and recruitment monitoring of spiny lobsters and crabs, but they have only been used in a limited way with clawed lobsters. For nearly two decades, diver-based suction sampling has served to monitor spatial-temporal patterns of American lobster (Homarus americanus) postlarval settlement and early juvenile abundance in shallow near-shore nurseries. Collectors could reveal settlement patterns in zones beyond the practical limits of diving. In 2005, we l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 26 publications
(24 reference statements)
1
20
0
Order By: Relevance
“…Each collector is fitted with a bridle to permit lifting in a horizontal position, which is important to retaining collections during retrieval. In previous pilot studies, we demonstrated that losses of organisms were negligible when the collectors were retrieved in this way (Wahle et al 2009b). Once on deck, the wire mesh covers are removed from the collectors.…”
Section: Sampling Methods and Geographic Coveragementioning
confidence: 99%
See 4 more Smart Citations
“…Each collector is fitted with a bridle to permit lifting in a horizontal position, which is important to retaining collections during retrieval. In previous pilot studies, we demonstrated that losses of organisms were negligible when the collectors were retrieved in this way (Wahle et al 2009b). Once on deck, the wire mesh covers are removed from the collectors.…”
Section: Sampling Methods and Geographic Coveragementioning
confidence: 99%
“…Collectors were primarily designed to evaluate lobster settlement in locations that are either unsafe or impractical for diver sampling, although they have become the preferred sampling device, even in shallow water, in some regions. Details of their design and method of deployment are provided in Wahle et al (2009b). Collectors are made of 10-gauge vinyl-coated wire with a 38-mm (1.5 inch) mesh.…”
Section: Sampling Methods and Geographic Coveragementioning
confidence: 99%
See 3 more Smart Citations